Respuesta :
Answer:
3x² -4x +12
Step-by-step explanation:
This involves straightforward application of the distributive property
x(2x+3)+(x-3)(x-4)
= 2x² +3x +x(x -4) -3(x -4)
= 2x² +3x +x² -4x -3x +12
= 3x² -4x +12
Answer:
f(x) = 3x^2 - 4x + 12
Step-by-step explanation:
First, let's label the expression and do a little housekeeping:
X(2x+3)+(x-3)(x-4) should be f(x) = x(2x+3)+(x-3)(x-4).
If we perform the indicated multiplication, we get:
f(x) = 2x^2 + 3x + (x^2 - 7x + 12), or
f(x) = 2x^2 + 3x + x^2 - 7x + 12. Combine like terms to obtain:
f(x) = 3x^2 - 4x + 12